KONSEP BELAJAR DALAM ISLAM - M. As’ad Nahdly; Ahmad Amiq Fahman (MIYAH : Jurnal Studi Islam, 2021)
Learning is a series of mental and physical activities to obtain a change in behavior as a result of an individual's experience in interaction with environment concerning cognitive, affective, and psychomotor. Learning strategies and learning methods are two different concepts but they are related to one another. Education is also one of the dimensions in Islamic circles. Various sides of education are discussed in Islam because education is not unidirectional, which only thinks of the transfer of knowledge as a measure of success. But also various other sides such as theories, principles, learning strategies, learning methods, which are related to learning. This study uses library research (library research). And the data search was carried out by looking at several Islamic history books and various other sources. This study aims to determine the definition of learning, strategies, concepts, methods and principles of learning from an Islamic perspective.Keywords: Learning Concept, Islam